Desain dan Analisis Bracket Winch Car Kendaraan Taktis 4x4 Menggunakan Metode Elemen Hingga - Pratama, Muhammad Rizky; Awom, Ilan Ramond; Ramang R, Dhanny; Pratama, M Daffa Agung; Daffa Muhammad Fauzan (VISA: Journal of Vision and Ideas, 2025)
This research designs and analyzes the Bracket Winch Car for a 4x4 tactical vehicle. The Finite Element Method (FEM) is used to obtain the stress results, followed by calculating the Safety Factor using CAD software. The Bracket Winch Car design, made from AISI 4340 material, demonstrates the ability to safely withstand the load of the WARN VR EVO 10-S winch. Simulations are conducted with loading conditions corresponding to the maximum pull weight of the winch, with a value of 44,452.8 N. The safety factor obtained is 1.695, indicating that the design is safe and suitable for use in tactical vehicles.